THE SECRET I.ANGUAGE OF THE INCAS (FICTION AND REALITY) IN THE COMENTARIOS REALES - Coello, Oscar (2009)
Sorne texts by Garcilaso in which he himself talks about his mastery of the generallanguageof the incas, and of what he calls the secret language of the solar dynasty are hereexposed. Then these declarations are set within the fictional and artistic constructionwhich elevated him ro glory.